The Effect of Compensation, Work Environment, and Career Development on Employee Turnover Intention of PT XYZ Final Assembly Department - Andrie Widya Atmoko; Anton Budi Santoso (CV. Publikasi Indonesia, 2024)
This research aims to analyze the effect of compensation, work environment, and career development on turnover intention among employees in the Final Assembly Department at PT XYZ. Involving 87 respondents who are employees of the department, this research employs a saturated sampling method for sample selection. Data collection is conducted through the distribution of questionnaires using Google Form. Analysis is performed using Multiple Linear Regression Analysis, with t and f statistical tests to test hypotheses. The results indicate that compensation, work environment, and career development partially have a significant negative effect on employees' intention to leave their jobs. Additionally, simultaneously, these three factors also have a significant impact on turnover intention. This study provides a deeper understanding of the factors affecting turnover intention among employees in the Final Assembly Department PT XYZ, and it offers important implications for human resource management in efforts to retain competent and quality employees.